Análise organizacional de acidentes de trabalho no setor de distribuição de energia elétrica - Silva, Alessandro José Nunes da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Brazilian electricity sector is one of the leaders in fatal work accidents. Total accidents number between 1999 and 2013, for instance, is 4.8 times bigger than those of other formal sectors of economy in Brazil. Technology systems and work organization in this sector are complex, and work conditions are dangerous, frequently resulting in work accidents. Objective: To analyze the influence of managerial and organizational choices at the Brazilian electricity sector on work safety. Method: series of cases study based on interviews and focal groups with key role-players, documental analysis and work observation, as well as reanalysis of work accidents in the distribution sector guided by concepts adopted in the method Accidents Analysis and Prevention Model (MAPA). Results: Interviews indicate that, in the electricity sector, economy is guided by financial logic of very short time results and that outsourcing is one of the guiding lines of job insecurity. Variability analysis showed flaws in human resources management by allowing the employment of subcontractors which were not protected, from the cognitive point of view, in order to carry out maintenance work in electrified environment. In all cases, the barrier analysis showed that safety management did not highlight interventions in the vicinity of energized primary line (high voltage) as being a potentially risky or dangerous situation. Changes analysis indicated the contribution of flaws in materials management and maintenance for the accidents, also influenced by quality and performance assessment adopted by the National Regulatory Authority, which determine uninterrupted power supply at the expense of safety. Discussion: The interviews of trade union leaders, as well as the cases analysis, indicated a weakening process of workers communities, which result in dilution and devaluation of practical knowledge and experiences. This study offers technical and organizational ...

Introdução: O setor elétrico brasileiro é um dos que mais causa acidentes fatais no país. A acidentalidade de 1999 a 2013 é, em média, 4,8 vezes maior que a dos demais setores formais da economia no Brasil. Sabe-se, também, que se trata de setor com sistemas complexos em termos de tecnologia e organização do trabalho cujas condições de trabalho são perigosas, resultando, frequentemente, em acidentes de trabalho. Objetivo: Analisar aspectos da influência de escolhas gerenciais e organizacionais do setor elétrico brasileiro na segurança do trabalho. Metodologia: Estudo de série de casos apoiado em entrevistas e grupo focal com atores-chaves, análise documental e observação em locais de trabalho, e re-análises de acidentes de trabalho do setor de distribuição guiadas por conceitos adotados no modelo de análise e prevenção de acidentes (MAPA). Resultados: As entrevistas apontaram que, no setor elétrico, a economia está comandada pela lógica financeira sustentada no curtíssimo prazo e que a terceirização é um dos fios condutores da precarização do trabalho. Análise de variabilidades mostrou falhas na gestão pessoal por permitir contratação de terceiros desprotegidos cognitivamente para realizar manutenção em ambiente de prevalência de lógica de oferta de energia. Em todos os casos a aplicação da análise de barreiras mostrou contribuições da gestão de segurança com destaque para intervenções ocorrendo nas proximidades de linha primária (alta tensão) energizada que não era apontada como fonte potencial de perigo ou risco. Análises de mudanças mostraram contribuições com origens em falhas na gestão de materiais e de sua manutenção também influenciados por critérios de avaliação de qualidade e desempenho adotados pela Agência Reguladora Nacional que privilegiam oferta ininterrupta de energia em prejuízo da segurança. Discussão: O enfraquecimento de coletivos...
Keywords: Saúde do trabalhador; Analise organizacional; Prevenção de acidentes; Sistemas de energia eletrica; Eletricidade - Acidentes; Electric power systems; Occupational Healtht